Narrowband Ultraviolet B Treatment in Skin Diseases Beyond Vitiligo, Psoriasis and Mycosis Fungoides - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2009)
Narrowband ultraviolet B, with its nonspecific immunmodulatuar actions, is a potential treatment alternative in many skin diseases. Various studies have shown its effects in psoriasis and vitiligo, treatment protocols have been developed especially for psoriasis. Apart from these, narrowband ultraviolet B is used as first-line therapy in skin conditions that are common in clinical practice. However, its efficacies in such diseases are not very well-known. The effects of narrowband ultraviolet B in atopic dermatitis, pityriasis lichenoides, lichen planus, pruritus, chronic urticaria, symptomatic dermographism and polymorphic light eruption are discussed here in light of the literature data. (Turkderm 2009; 43: 83-8)
Keywords: Narrowband ultraviolet B; phototherapy; RANDOMIZED CONTROLLED-TRIAL; POLYMORPHIC LIGHT ERUPTION; AIR-CONDITIONED PHOTOTHERAPY; CHRONIC ATOPIC-DERMATITIS; PITYRIASIS LICHENOIDES; UVB PHOTOTHERAPY; CHRONIC URTICARIA; PLANUS; ECZEMA; EXPERIENCE